2016
DOI: 10.4014/jmb.1506.06073
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of Thymol on AGS Human Gastric Carcinoma Cells

Abstract: Numerous plants have been documented to contain phenolic compounds. Thymol is one among these phenolic compounds that possess a repertoire of pharmacological activities, including anti-inflammatory, anticancer, antioxidant, antibacterial, and antimicrobial effects. Despite of the plethora of affects elicited by thymol, its activity profile on gastric cancer cells is not explored. In this study, we discovered that thymol exerts anticancer effects by suppressing cell growth, inducing apoptosis, producing intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 35 publications
6
55
0
Order By: Relevance
“…Several studies are available for the antifungal effects that could explained our results, and for A. abrotanum, the plant showed that activity against C. albicans [19]. These effects could be due to the active constituents that in the essential oil of the plant which they have an antifungal action such as borneol [20] and camphor [21], which may be explained the results in this work.…”
Section: Resultssupporting
confidence: 49%
“…Several studies are available for the antifungal effects that could explained our results, and for A. abrotanum, the plant showed that activity against C. albicans [19]. These effects could be due to the active constituents that in the essential oil of the plant which they have an antifungal action such as borneol [20] and camphor [21], which may be explained the results in this work.…”
Section: Resultssupporting
confidence: 49%
“…The beneficial effects in these cells were attributed to the generation of intracellular ROS, depolarization of mitochondrial membrane potential, apoptosis and impeding cell growth via intrinsic mitochondrial pathway and the activation of pro-apoptotic mitochondrial proteins; caspases, Bax and PARP (Kang et al, 2016). …”
Section: Thymol In Cancer Cellsmentioning
confidence: 99%
“…In this study, three kinds of monoterpenes: thymol, linalool, and menthol, were and menthol exhibited anti-cancer effects against human tumor cell lines, such as prostate cancer [19,20], malignant melanoma [21], colon cancer [22], and gastric cancer [23]. They suppressed cell growth and induced apoptosis in tumor cells in a time-and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%